LITERATURE REVIEW: PERAN KEPEMIMPINAN DALAM MANAJEMEN PERUBAHAN DI ORGANISASI - Nunu Pertiwi; Hanung Eka Atmaja (Jurnal Ekonomi dan Bisnis (EK dan BI), 2021)
Organizational leaders are the determinants of the direction of a change so that to plan and implement organizational change, strong leadership is needed through leadership actions in influencing and directing organizational members to achieve change. This study aims to describe the role of leadership in change management in an organization. The method used is literature review. The results of this study are the importance of the role of leadership in management change. Change needs to be designed, engineered and managed by a strong, visionary, intelligent and developmental leadership.